The Concept of Wages in the Maqashid Sharia Overview (Study of PP No. 36 of 2021) - Wibawa, Muhammad Dimas; Gassing, Abd. Qadir; Hamsir, Hamsir (Pascasarjana UIN Alauddin Makassar, 2023)
The objectives of this study are to: 1). Describe and analyze the concept of wages regulated by the government, 2). Discover workers/laborers response to government-regulated wages, and 3). Describe and analyze the government-regulated concepts based on the approach of the two main elements in maqashid sharia, such as hifzu an-nafs and hifzu al-māl. The author used a multidisciplinary approach to overcome the problems, namely a linguistic approach, normative juridical, and qualitative-descriptive methods to collect the data. This study was classified as library research; the data collected was analyzed using content analysis on literature that is representative and has relevance to the problem, then the comparison using comparative analysis was reviewed and concluded. After reviewing and analyzing policies in the form of established concepts, the wage provisions regulated by the government in law aim to provide a sense of justice for workers/laborers and align with the main principles in maqashid sharia. Even though Islam does not explicitly state the amount of wages in detail, it strictly requires anyone who provides work to pay wages/salaries to their workers. After reviewing the existing concepts, some problems were identified that need effort to resolve.